All Days 2012
DOI: 10.2118/154665-ms
|View full text |Cite
|
Sign up to set email alerts
|

Polymer Flooding in a Large Field in South Oman - Initial Results and Future Plans

Abstract: In heavy oil reservoirs, water flooding leaves behind unswept hydrocarbon volumes due to unfavourable mobility ratios resulting in low ultimate recoveries. Increasing the viscosity of the injected water using polymer improves the water-oil mobility ratio resulting in improved recovery factors. This paper discusses for a large field in South Oman the successful implementation of a polymer flood project, the early results of Phase I and the planned expansions to Phase II and Phase III. Following a number of fiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(13 citation statements)
references
References 4 publications
0
10
0
1
Order By: Relevance
“…First, for many of the largest polymer floods (e.g., Daqing, Shengli, Pelican Lake), no effort was made to eliminate dissolved oxygen or control oxidation in the injected polymer solutions. Because these low-temperature polymer floods were quite successful in recovering oil (Wang et al 2008(Wang et al , 2011Zhu et al 2013;Delamaide et al 2014), it seems likely the HPAM polymers did not suffer severe degradation. Manichand et al (2013) demonstrated that HPAM solutions propagated more than 300 ft through a reservoir (at 38 C) with no significant degradation even though the injected solutions were saturated with dissolved oxygen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, for many of the largest polymer floods (e.g., Daqing, Shengli, Pelican Lake), no effort was made to eliminate dissolved oxygen or control oxidation in the injected polymer solutions. Because these low-temperature polymer floods were quite successful in recovering oil (Wang et al 2008(Wang et al , 2011Zhu et al 2013;Delamaide et al 2014), it seems likely the HPAM polymers did not suffer severe degradation. Manichand et al (2013) demonstrated that HPAM solutions propagated more than 300 ft through a reservoir (at 38 C) with no significant degradation even though the injected solutions were saturated with dissolved oxygen.…”
Section: Discussionmentioning
confidence: 99%
“…This approach was applied in some field applications. In particular, the polymer flood at Marmul uses a free-radical scavenger formulation (Koning et al 1988;Al-Saadi et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The recent rise in oil price has initiated a renaissance of the technique among the international oil companies with applications underway in Angola [65] and Oman [66] as well as many being planned for other regions including the UK North Sea [67]. …”
Section: Polymer Floodingmentioning
confidence: 99%
“…The polymer-flood project is implemented in phases. Phase 1 of the project, that is currently in operation, is targeting areas in which reservoir characteristics are similar to those in the initial polymer pilot (Teeuw et al 1983;Koning and Menzter 1988). Polymer injection takes place through 20 inverted nine-spot patterns, four inverted five-spot patterns all with vertical injectors, and three additional patterns with horizontal injectors.…”
Section: Field Overviewmentioning
confidence: 99%